Patient Perspective on Post-Breast Reconstruction Exercise and Physical Therapy. (December 2021) - Higgins, Margaret J.; Kale, Nisha; Homsy, Christopher; Alabaster, Kelsey L.; Ferrin, Peter; Miskimin, Cadence; Chaffin, Abigail E.; Mulcahey, Mary K.
Abstract: Background: Breast reconstruction may result in significant functional compromise and pain. Postoperative exercise and physical therapy can mitigate these morbidities, but it is infrequently recommended by healthcare providers. This study asked how many breast reconstruction patients are instructed to perform postoperative at-home exercises or physical therapy, how many reported following through with these instructions, and what timeline they were given for these activities. Methods: A 16-question multiple-choice anonymous online survey was distributed to a private breast cancer survivor Facebook group (Diep C. Foundation). Results: A total of 150 breast reconstruction patients responded to our survey. The majority of respondents in our sample were not provided with specific instructions regarding postoperative at-home exercises ( N = 70, 54.3%) or physical therapy ( N = 77, 63.6%). Approximately 13 of 59 respondents (22%) who had been instructed to participate in postoperative at-home exercises were directed to begin at 2–3 weeks. Approximately 15 of 44 respondents (34.1%) who had been instructed to participate in physical therapy were directed to begin these at 4–5 weeks. Conclusions: To the best of our knowledge, this is the first study of how often postoperative at-home exercises and physical therapy are recommended to breast reconstruction patients. Despite robust evidence of these activities' benefits, most women are not instructed to participate in postoperative at-home exercises or physical therapy. This is likely to impede breast reconstruction patients' recovery and delay their return to activities of daily living. More studies are needed of how to actively engage breast reconstruction patients in postoperative at-home exercises and physical therapy.